2019
DOI: 10.1021/acs.jpcc.9b03822
|View full text |Cite
|
Sign up to set email alerts
|

Water (Non-)Interaction with MoO3

Abstract: Molybdenum(VI) oxide (MoO 3 ) is used in a number of technical processes such as gas filtration and heterogeneous catalysis. In these applications, the adsorption and dissociation of water on the surface can influence the chemistry of MoO 3 and thus the course of heterogeneous reactions. We use ambient pressure X-ray photoelectron spectroscopy to study the interaction of water with a stoichiometric MoO 3 surface and a MoO 3 surface that features oxygen defects and hydroxyl groups. The experimental results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The results at low RH and high RH resemble that seen in other oxides and follow a similar pattern [14][15][16]18,42 with notable exceptions. 20 At low RH (below ∼10 −3 ), water dissociates to form OH groups, which on STO should create Ti−OH and a neighboring O b H on the defect-free surface. While hydroxylation of the surface saturates at high RH (above ∼10 −1 RH), water layers grow above it.…”
Section: ■ Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results at low RH and high RH resemble that seen in other oxides and follow a similar pattern [14][15][16]18,42 with notable exceptions. 20 At low RH (below ∼10 −3 ), water dissociates to form OH groups, which on STO should create Ti−OH and a neighboring O b H on the defect-free surface. While hydroxylation of the surface saturates at high RH (above ∼10 −1 RH), water layers grow above it.…”
Section: ■ Experimental Resultsmentioning
confidence: 99%
“…13 Ambient pressure X-ray photoelectron spectroscopy (AP-XPS) provides a unique opportunity to investigate the surface under increasing ambient relative humidity (RH), where the first hydration layer accrues on the surface from vacuum conditions. This technique has been utilized to studying hydroxide (OH) and water (H 2 O) coverages on transitionmetal oxides, such as TiO 2 , 14,15 MgO, α-Fe 2 O 3 , 6,18 Cu 2 O, 19 Al 2 O 3 , CoOOH 5 , MoO 3 , 20 Sr 2 Co 2 O 5 , 21 and LaCoO 3 , 22 among many other material surfaces.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[56] Water dissociation and chemical reactions are enhanced on defective surfaces in comparison to defect-free ones. [57,58] Interestingly, the electrochemical measurements indicate a higher activity of the (100) surface towards the hydrogen adsorption reaction. Indeed, in Fig.…”
Section: Adsorption In An Electrolytementioning
confidence: 99%
“…The same model surface containing an O vac and hydroxyl groups approximates the experimental surface characterized with XPS . Our prior work found that small amounts (we estimate ∼5% of a monolayer, just above the detection limit of XPS) of molecular water adsorb to the MoO 3 under the humid conditions used in gas filtration, so the interaction between NO 2 and a MoO 3 (010) surface with adsorbed water molecules was also investigated. The most stable geometric configurations are depicted in Figure , and the corresponding energies are listed in Table .…”
Section: Resultsmentioning
confidence: 99%